Analisa Keselamatan dan Kesehatan Kerja pada Proses Pemuatan Crude Oil di Single Buoy Mooring Tuban Marine Terminal - Janes Ginting, Harjun; Noviarianto, Noviarianto; Bayu Wantoro, Widar (Jurnal Maritim Polimarin, 2023)
Single Buoy Mooring (SBM) is a means for mooring tankers to carry out loading or unloading operations through SBM located on the high seas. SBM serves to facilitate loading or unloading crude oil by connecting the installation on land through pipes connected to the SBM system on the high seas. The thing that is considered so that the mooring process runs safely is by minimizing the factors and hazards that cause the mooring process to be hampered. the danger at the time of loading at SBM is during the process of mooring the ship and the danger of H2S gas contained in curde oil. During the loading of crude oil, the cargo must always be checked for H2S gas levels in crude oil, this gas is quite dangerous when exposed directly to H2S gas. It can cause loss of smell, eye irritation, shortness of breath, unconsciousness and death. This thesis research method is a qualitative descriptive method by analyzing the problem using Hazard Identification, Risk Assessment, Risk Control (HIRARC).